Patent Review on Plasma Polishing - Wang, Ru; Li, Guo (Recent Patents on Engineering, 2025)
Atmospheric plasma polishing technology is an essential technology in the nanoscale machining needs of aerospace, astronomical telescopes, and other related fields and is an important means to expand ultra-precision machining technology in the future. However, in the research of surface cleaning, cost, equipment, etc., there are still some technologies that need to be broken through in order to better use plasma polishing technology in the future. Through the introduction and discussion of the patent characteristics of plasma polishing in recent years, some valuable conclusions are summarized, and future research and development are prospected. The patents of plasma polishing were studied, and the patent and research progress of plasma polishing were summarized. With the development of ultra-precision machining technology, plasma polishing technology has become more and more important. Therefore, plasma polishing technology is needed to achieve low-cost and high-efficiency processing of ultra-precision materials. The importance of plasma polishing technology is discussed by describing its working characteristics. By comparing these patents, it is concluded that atmospheric plasma polishing technology is the main development trend of ultra-precision machining technology in the future.
Keywords: ultra-precision machining